Franco Fortini. La testimonianza attraverso la Cina - Del Castillo, Ludovica (L’ospite ingrato, 2024)
In 1955, Franco Fortini travelled with the first Italian delegation to the People’s Republic of China, accompanied by Antonicelli, Bernari, Cassola, and Trombadori, among others. The result of this experience is the reportage Asia Maggiore, which becomes emblematic of that journey and, more generally, of the sense of attestation. The aim of this essay is to explore the value of testimony for Franco Fortini, which, in the case of China, is expressed in the form of reportage. Central to this analysis is the focus on the mediation between political reality and literature, and at the same time, between the attempt to understand as objectively as possible and the awareness of the declared partiality of one’s own perspective, in recognition of the inevitable filter assumed by every observer. This dichotomy is also expressed in the reading of China both as an “allegorical geography” and as an opportunity for material verification, with the goal of modifying the original reality, and thus in a continuous dialogue and mediation between reality and literary form.